SISTEM MONITORING DAN SISTEM PENYEIMBANG BERAT MUATAN KAPAL FERRY SEBAGAI ANTISIPASI KECELAKAAN - Saputra, Azhar Aulia; Mardianto, Endi; Adikoro, Ahmad Harits (Program Kreativitas Mahasiswa - Teknologi, 2013)
Shipwreck is influenced by several factors, namely the ship and the port system is less than optimal, assuming good weather conditions. Invention at the port is to improve the performance of the port in knowing overweight and balance boatload of ships so as to avoid the possibility of accidents due to problems on the ship and the port. System improvements in the detection port charge balance on the ship using imu acellero Arduino board to detect the slope. Lab scale testing condition for sending and receiving data between a boatload of weight and handheld hardware android.Pengiriman angle of the data on the microcontroller via bluetooth at a distance of 30 meters with an average error 0.5%. Data on the equilibrium angle detection using imu acellero Arduino board has an average error 2.0%.